1997
DOI: 10.1104/pp.115.4.1385
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Proliferation-Induced Genes in Arabidopsis thaliana (Characterization of a New Member of the Highly Evolutionarily Conserved Histone H2A.F/Z Variant Subfamily)

Abstract: New tissues and organs are generally initiated throughout the life of the plant from small, highly organized groups of cells called meristems (Medford, 1992). Occasionally, however, adventitious organ development occurs as a consequence of the reactivation of cell division in previously quiescent cells of differentiated tissues (Yang et al., 1994). A better understanding of how developing plants achieve such a tight control of proliferative activity in meristematic and differentiated tissues will come from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 62 publications
0
29
0
1
Order By: Relevance
“…It is therefore not surprising that we identify potential stress-associated genes within this cluster including chitinases, peroxidase, glutathione transferase, proteolysis (F-box protein, serine carboxypeptidase), and heat shock-related proteins (see Tables I-IV for details). Nevertheless, we also observe expression of genes likely to be involved in S phase, such as histone H2A.F/Z already known to be cell cycle-regulated at the G 1 /S boundary in Arabidopsis suspension cultures (29), proliferating cell nuclear antigen (cluster 11), and a DNA cytosine methyltransferase (cluster 12), which these results suggest are regulated genes. In sub-branch B, a large group of genes (147 genes) is found showing a peak of expression at 2 h after the block is released, corresponding to early to mid-S phase, including several genes involved in DNA metabolism and replication such as histones, a CDC50 homologue, and FAS1, which shows strong periodic regulation in cluster 4 (67).…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…It is therefore not surprising that we identify potential stress-associated genes within this cluster including chitinases, peroxidase, glutathione transferase, proteolysis (F-box protein, serine carboxypeptidase), and heat shock-related proteins (see Tables I-IV for details). Nevertheless, we also observe expression of genes likely to be involved in S phase, such as histone H2A.F/Z already known to be cell cycle-regulated at the G 1 /S boundary in Arabidopsis suspension cultures (29), proliferating cell nuclear antigen (cluster 11), and a DNA cytosine methyltransferase (cluster 12), which these results suggest are regulated genes. In sub-branch B, a large group of genes (147 genes) is found showing a peak of expression at 2 h after the block is released, corresponding to early to mid-S phase, including several genes involved in DNA metabolism and replication such as histones, a CDC50 homologue, and FAS1, which shows strong periodic regulation in cluster 4 (67).…”
Section: Resultsmentioning
confidence: 79%
“…Removal of the inhibitor by washing leads to release of the block and the synchronous resumption of S phase and progression through the cell cycle. However, Arabidopsis cell culture systems have proven remarkably recalcitrant to efficient synchronization using this or other methods (29,55,56). We recently developed techniques for aphidicolin synchronization of the Arabidopsis Landsberg erecta cell line MM2d (22), which was used for the synchronization experiments reported here.…”
Section: Resultsmentioning
confidence: 99%
“…Arabidopsis H2A-8, -9, and -11 are similar to H2A.F/Z variants, whereas H2A-3 and H2A-5 show strong similarity to H2AX variants. Callard and Mazzolini (1997) reported that the expression of Arabidopsis H2AvAt (HTA11), a H2A.F/Z variant, is tightly related to cell proliferation. They suggested that expression of HTA11 might be associated with a switch from a quiescent to an actively replicating state.…”
Section: Arabidopsis Histone H2a Genesmentioning
confidence: 99%
“…Arabidopsis HTA8 shows an expression pattern expected of a core histone in that its expression is restricted to meristematic cells. The expression of another Arabidopsis H2A.F/Z variant, cH2AvAt (HTA11), is tightly correlated with cell proliferation in cell suspension cultures (Callard and Mazzolini, 1997).…”
Section: Differential Expression Of Histone H2a Members In Arabidopsismentioning
confidence: 99%
See 1 more Smart Citation